Atomic Revealing of the Dissolution Behavior of Spinel Oxides on the 316L Surface in Alkaline High-Temperature and High-Pressure Water - Bin Zhang; Congbin Zhu; Xiaoping Zou; Haodong Wu; Jian Xu (Metals)
The structure and composition of the oxide layer on the surface of 316L stainless steel (SS) after exposure to alkaline high-temperature and high-pressure water for 2000 h are characterized using various analytical techniques. The oxide layer has a double-layer structure comprising an outer spinel oxide and an inner Cr oxide. With an increase in exposure time, the thickness of the inner oxide layer increases and stabilizes at approximately 100 nm. The spinel oxide dissolves after 336 h of exposure, and the dissolution increases with increasing exposure time. The adsorptive capacity of OH− on the NiFe2O4 surface is explained using density functional theory (DFT) calculations. The energy released by the strong adsorption of OH− on the surface of NiFe2O4 provides the impetus for the dissolution of NiFe2O4, so that NiFe2O4 dissolves in the experimental environment.